1994
DOI: 10.1007/bf01534426
|View full text |Cite
|
Sign up to set email alerts
|

Unprimed CD4+ and CD8+ T cells can be rapidly activated by a CD3×CD19 bispecific antibody to proliferate and become cytotoxic

Abstract: We previously reported that a CD3 x CD19 bispecific antibody (bsAb) can induce efficient killing of tumour cells by preactivated T cells isolated from patients with B cell malignancy. For future intravenous application we investigated whether resting T cells from peripheral blood can be stimulated to proliferate and become cytotoxic with the CD3 x CD19 bsAb alone. Indeed peripheral blood mononuclear cells, isolated from healthy donors or patients with B cell malignancy, started to proliferate within 1 day in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…Previous studies with a CD19 Â CD3 diabody showed that after 4-hour incubation largely CD8 + but not CD4 + T-cells mediate redirected cell lysis, 25 whereas at longer incubation times also CD4 + cells were activated for tumor cell lysis. 26,27 A similar result was obtained with an Ep-CAM Â CD3 bispecific single chain antibody, where it was shown that CD4 + T-cells could substantially contribute to redirected target cell lysis, yet with a delayed reaction compared with CD8 + cells. 28,29 In our experiments, 24-hour incubation before the first measurements seems to suffice for the CD4 + cells to reach comparable levels of lysis as the CD8 + cells.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies with a CD19 Â CD3 diabody showed that after 4-hour incubation largely CD8 + but not CD4 + T-cells mediate redirected cell lysis, 25 whereas at longer incubation times also CD4 + cells were activated for tumor cell lysis. 26,27 A similar result was obtained with an Ep-CAM Â CD3 bispecific single chain antibody, where it was shown that CD4 + T-cells could substantially contribute to redirected target cell lysis, yet with a delayed reaction compared with CD8 + cells. 28,29 In our experiments, 24-hour incubation before the first measurements seems to suffice for the CD4 + cells to reach comparable levels of lysis as the CD8 + cells.…”
Section: Discussionsupporting
confidence: 70%
“…It has been shown for BiTEs and other bispecific molecules that they function as adaptor molecules between the T and the tumor cells that bring them closer together and trigger activation of the signaling cascade of the T cell receptor (TCR) complex facilitated by the binding of the bispecific abs to the CD3 component of the receptor (Figure 3A). Since the activation is based on CD3 and not on the highly variable TCR, bispecific abs can redirect all antigen experienced CD4 + and CD8 + T cells [91,[127][128][129][130] in the patient against the aberrant cells independent of their specificity. The activation of the T cells results only from the polyvalent ligation of CD3 [70,90] that induces the formation of a transient cytolytic synapse between the cytotoxic T cells and the target cells ( Figures 3B and 4) [104,131].…”
Section: Mechanism Of Action Of the Bispecific Antibodiesmentioning
confidence: 99%
“…1996). Others did not observe activation of CD4 ϩ T cells (Haagen et al, 1994). The discrepancy may possibly depend on the application regimen.…”
Section: Discussionmentioning
confidence: 97%